Problematic Student Identification and Visualization in The Counseling Activites - Evaliata Br Sembiring (JAICT, 2018)
The counseling activities are procedures carried out by academic advisers to identify problematic students, especially in their academic learning process. Students are categorized as problematic when they do not submit their KRS, have a lower GPA than the college standard, have not yet paid their due, or receive warning letters owing to their misconducts. The current system provides every students’ data but academic advisers still need to identify every problematic students’ data one by one. A working solution would be to present the data in a visualization, so the problematic students along with their problem category can be identified automatically. The application employs the UML approach in its planning and web-based application development tools in its implementation. Highchart is implemented in the data visualization. The resulted application boasts the student data management feature to help the problematic student identification process. This feature automatically identifies the problematic students on each term by visualizing it in a colored charts and tables.